Biography of X : a novel - Lacey, Catherine, 1985- (Farrar, Straus and Giroux, 2023)
"When X - an iconoclastic artist, writer, and polarizing shape-shifter - falls dead in her office, her widow, wild with grief and refusing everyone's good advice, hurls herself into writing a biography of the woman she deified. Though X was recognized as a crucial creative force of her era, she kept a tight grip on her life story. Not even CM, her wife, knew where X had been born, and in her quest to find out, she opens a Pandora's box of secrets, betrayals, and destruction. All the while, she immerses herself in the history of the Southern Territory, a fascist theocracy that split from the rest of the country after World War II, as it is finally, in the present day, forced into an uneasy reunification." -- Publisher annotation.